Effect of thyroid function on assisted reproduction outcomes in euthyroid infertile women: A single center retrospective data analysis and a systematic review and meta-analysis - d’Assunção, Viviane Rosado Negreiros; Montagna, Erik; d’Assunção, Luis Eduardo Negreiros; Caldas, Maria Madalena Pessoa; Christofolini, Denise Maria; Barbosa, Caio Parente; Negreiros, Ricardo Andre Medeiros; Laganà, Antonio Simone; Oliveira, Renato de; Bianco, Bianca (Frontiers in Endocrinology, 2022)
Background: The influence of thyroid-stimulating hormone (TSH) on gestational outcomes have been studied and checked whether differing TSH levels are relevant on human reproduction outcomes. International guidelines recommend TSH values <2.5 mIU/L in women trying to conceive, since values above this level are related to a higher frequency of adverse reproductive outcomes. This study aimed to evaluate whether TSH values correlate with different gestational outcomes in euthyroid infertile women without autoimmune thyroid disease. Methods: A retrospective cohort study was conducted involving 256 women who underwent in vitro fertilization (IVF) treatment. The participants were divided into two groups: TSH 0.5-2.49 mIU/L (n=211) and TSH 2.5-4.5 mIU/L (n=45). The clinical data, hormonal profiles and reproductive outcomes were compared between groups. Additionally, a systematic review with meta-analysis following the PRISMA protocol was carried out in PubMed/MEDLINE, EMBASE, and SciELO, with no time or language restrictions, for articles comparing TSH groups named “low TSH” (<2,5 mIU/L) and “high TSH” (≥2.5 mIU/L). A meta-analysis of proportions was performed with pooled estimates expressed as relative risk (RR) of events and a random effects model. Results: Age, BMI, free thyroxine levels (FT4) hormonal profile and IVF outcomes were not different between groups, neither gestational outcomes (p=0.982). Also, no difference was observed when the TSH and FT4 levels were compared between patients with positive or negative gestational outcomes (p=0.27 and p=0.376). Regarding the systematic review with meta-analysis, 17 studies from 2006 to 2022 were included, and added by this original retrospective research comprising 13.247 women undergoing IVF. When comparing the proportions of clinical pregnancy between the TSH groups, no significant difference was found (RR 0.93, 95% CI 0.80–1.08), with high between studies heterogeneity (I²: 87%; τ2: 0.0544; p<0.01). The number of deliveries was not significantly different between groups, despite a trend towards higher frequency in the high-TSH group (RR 0.96, 95% CI 0.90–1.02). Conclusion: Variation in TSH levels within the normal range was not associated with pregnancy and delivery rates in women, without autoimmune thyroid disease, who underwent IVF treatment. Systematic review registration: CRD 42022306967.